Elementos de uma teologia da ecologia: aspectos ecológicos dos projetos Lachares e Capa no contexto da Igreja Evangélica de Confissão Luterana no Brasil - Sieben, Marcelo (2010)
Theology of the Earth arises in the 70 s as an initiative of the churches in Latin America who had been facing the reality of emerging problems in the countryside for a long period. Alike Liberation Theology, the Theology of the Earth approached, through its methodology, the socio-historical analysis through which it was possible to observe the emergency of an ecological reflection and its gradual developments up to the current days. In the Evangelical Lutheran Church in Brazil (IECLB) this Theology expressed itself through the organization and development of projects which sought to provide attendance, support and resistance to the small farmers so that they would keep living in the rural area. In 1978, in the sphere of the Third Ecclesiastical Region (RE III) of IECLB, northwest of Rio Grande do Sul (RS) state and western of Santa Catarina state, an organization called CAPA (Advice Center for Small Farmers; later, it was renamed and became Support Center for Small Farmers) was created, and its objective was to assist farmers with technical, economical, juridical, class and cooperation orientations. This approach also aimed at disseminating ecological alternatives to produce healthier food, which would be less dependent on industrialized products that made the costs rise. The effectiveness of CAPA is due to initiatives originated from the development of reflections on social changes in Brazil in the scope of IECLB and from the relationship with other churches. The Mission among indigenous people, the rural exodus, the landless farmers mobilization, which will result in the MST (Landless Farmers Movement), and the colonization of the New Areas, in the central-west and north of the country, became relevant issues in the meetings of ecclesiastical leaderships and laypersons in that period. The works of Sílvio Meincke, a pastor who served in the RE III, rescue aspects of this reflection which preceded the creation of the Center and its late dissemination in the southern region of Brazil. The creation of CAPA was also preceded by LACHARES (Home of Culture and Harmony of Social Reintegration), an initiative of Pastor Silvino Schneider which took place halfway through the decade of 1970 in Rancho Queimado county, Santa Catarina state. With catechetical formation, but serving as a pastor, Schneider first served in Burití, RS state. Both in Burití and in Rancho Queimado, he was always committed to promote changes in favor of the farmers. He noticed that the progress of modernization of agriculture had caused changes in the lives of those small farmers in Rancho Queimado and its region in terms of economical dependency on banks and commerce (fertilizers and chemical products). LACHARES started its activities in 1976 and in 1979 Schneider began publishing articles in the Evangelical Journal with the title of Theology of the Earth, contemplating the practices of this Home. The social-historical changes that precede these projects are shown in this research study and are based on studies concerning Agriculture and Environment History, as well as sources of Anthropology and Archaeology. Regional Literature appears in the thesis as an important source to find the environmental changes concerning agriculture. The ecology that underlies the practices disseminated by CAPA and by LACHARES focuses on studies about agricultural ecology. The reflection on Elements of a Theology of Ecology concerns the ecology that is practiced on small farms or through Family Farming and seeks to recover the theological foundations of transforming pastoral acts.